Comparison of patients’ satisfaction between ‘bulk trolley’ and ‘centralised plating’ food service systems in two government Hospitals in Selangor - Ramkumar, Sasirekha (Universiti Sains Malaysia, 2015)
Foodservice is regarded as one of the most important services of hospital services, as food plays a vital role in aiding patients’ recovery and wellbeing. This study aims to compare patients’ satisfaction between the ‘bulk trolley’ and ‘centralised plating’ foodservice systems in two government hospitals in Selangor (Ampang and Kajang hospitals). Cross-sectional study was conducted, whereby ‘The Acute Care Hospital Food Service Patient Satisfaction Questionnaire’ (ACHFSPSQ) comprising food quality, food provision, menu selection, meal serving time, staff attitude and environment was distributed to patients who were on normal diet. Likert scale was used to analyse the answers, where a mean score >3 indicated that patients were satisfied. Simple random sampling was used to recruit 230 patients (43.5% from bulk trolley and 56.5% from centralised). There were more female (n=124, 54%) than male (n=106, 46%) patients and majority were Malays (n=95, 41.3%). Regardless of the type of foodservice system, most of them indicated that hospital food was ‘good’ (53% in bulk-trolley and 57% in centralised). However, in both systems, patients were dissatisfied with the taste (mean=2.45 in bulk-trolley and 2.66 in centralised), empathy shown by staff (mean=2.37 in bulk-trolley and 2.11 in centralised), noise (mean=1.74 in bulk-trolley and 1.39 in centralised), smell (mean=1.30 in bulk-trolley and 1.24 in centralised) and cutlery conditions (mean=1.03 in bulk-trolley and 1.00 in centralised). Significant differences (p<0.05) in satisfaction between the two systems on food (presentation, temperature, portion size, serving time, food variety and menu selection was reported. Additionally, satisfaction with staff appearance, empathy and noises showed significant difference between bulk trolley and centralised plating system (p<0.05). Findings indicated that patients’ satisfaction certainly differed according the foodservice system used, which may affect their food consumption subsequently. Therefore, the foodservice system that optimizes patients’ food consumption should be implemented.